Development of ready-to-drink chocolate flavored mung bean (Vigna radiata) milk - Tiongson, Cleo Almira D.; Peralta, Justin Godfred B. (Quezon City College of Home Economics, University of the Philippines Diliman, 2019)
This study developed ready-to-drink chocolate flavored mung bean milk and analysed its physicochemical characteristics, proximate composition, microbial properties, stability, and economic value. The production process is composed of soaking of mung beans for 8-10 hours, dehulling using the floatation method, adding of cocoa powder, refined white sugar, and locust bean gum as stabilizer, blending, diluting, bottling, exhausting at 850C for 1 minutes, sealing, retorting at 2040C for 10 minutes, and cooling before storing. A consumer acceptance test was used to determine the more acceptable ratio of 33.3 g of mung bean per 1 L of water. Stability of the product was tested through 2 settle tests, a 3-day settle test for the formulation without stabilizers and a 24-hour settle test for formulations with LBG and gellan gum, and through a consumer acceptance test, resulting in locust bean gum being chosen as a more appropriate stabilizer for the product. Physicochemical characteristics of the final product had a pH of 7.89 indicating low acidity and more favorable conditions for microbial growth, TSS of 12.70Brix , and color values of L = 6.73, a=10.32, and b=7.14, indicating a very dark brown color. The crude protein, fat, moisture, total carbohydrates, ash, and calcium were determined through Kjeldahl Method, Acid Hydrolysis, Vacuum Oven Drying, Computation, Ignition, and AAS, respectively. Per 100 g of sample, the composition was 1.63 g of crude protein, 0.64 g of fat, 83.2 g of moisture, 13.69 g of total carbohydrates, 0.84 g of ash, and 9.79 mg of calcium, making it inferior to the nutritional profile of cow‟s milk and soy milk. Microbial analysis was also done to determine the plate counts of aerobic microorganisms (APC), yeast and molds, total coliform, E.coli, and Salmonella. All xii counts were determined to be within standards for a pasteurized product in need for refrigeration, indicating an effective process schedule and its safety for consumption.
Thesis Classification: F
Thesis (B.S. Food Technology)--University of the Philippines Diliman
Includes bibliographical references and appendices.
Keywords: Beans -- Philippines; Mung bean -- Philippines; Chocolate milk -- Philippines